2019
DOI: 10.1083/jcb.201905048
|View full text |Cite
|
Sign up to set email alerts
|

Yorkie and JNK revert syncytial muscles into myoblasts during Org-1–dependent lineage reprogramming

Abstract: Lineage reprogramming has received increased research attention since it was demonstrated that lineage-restricted transcription factors can be used in vitro for direct reprogramming. Recently, we reported that the ventral longitudinal musculature of the adult Drosophila heart arises in vivo by direct lineage reprogramming from larval alary muscles, a process that starts with the dedifferentiation and fragmentation of syncytial muscle cells into mononucleate myoblasts and depends on Org-1 (Drosophila Tbx1). Her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…VLMs originate during metamorphosis from alary muscles as part of a reprogramming process. Transformation of alary muscles is tightly controlled by the transcription factor Org-1 (Boukhatmi et al, 2014;Schaub et al, 2015;Schaub, Rose, & Frasch, 2019). Org-1 mutants fail to form alary muscles and therefore also VLMs, which results in malformations of the heart tube including myofiber misorientation in cardiomyocytes (Schaub et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…VLMs originate during metamorphosis from alary muscles as part of a reprogramming process. Transformation of alary muscles is tightly controlled by the transcription factor Org-1 (Boukhatmi et al, 2014;Schaub et al, 2015;Schaub, Rose, & Frasch, 2019). Org-1 mutants fail to form alary muscles and therefore also VLMs, which results in malformations of the heart tube including myofiber misorientation in cardiomyocytes (Schaub et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The new molecular details of this dedifferentiation process presented in this paper are about as startling as the discovery of anterior alary muscle reprogramming itself (6). In Drosophila , Yki and Myc activity are widely known to promote proliferation and prevent apoptosis in the developing brain, eye, and wing (7, 8).…”
mentioning
confidence: 77%
“…In this issue, now identify new molecular players that are responsible for this reprogramming (Fig. 1; 6). They present data showing that the reprogramming and disaggregation of larval anterior alary muscle, which is the first step in ventral longitudinal muscle formation, are regulated in concert by Hippo and JNK signaling pathways.…”
mentioning
confidence: 99%
“…One hypothesis was VLMs could form by fusion of adult myoblasts with AM fragments ( Curtis et al, 1999 ). AM fate and trans-differentaition into VLMs in Drosophila pupae has now been deciphered, using in vivo imaging, cell lineage and genetic analyses ( Schaub et al, 2015 ; Schaub et al, 2019 ). These authors showed that larval AM A1-A3 undergo a lineage reprogramming process without proliferation.…”
Section: Trans-differentiation Of Ams At Metamorphosismentioning
confidence: 99%
“…The number of nuclei per AM/TARM in L3 larvae is between 4 and 6 ( Bataillé et al, 2020 ), similar to the number at embryo hatching ( Boukhatmi et al, 2014 ; Rose et al, 2022 ), suggesting as for skeletal muscles the absence of nuclear divisions during larval development. Yet, the ability of at least a subset of multinucleate AMs to dedifferentiate into mononucleated alary muscle derived cells (AMDCs) and fuse with additional myoblasts during VLM formation ( Schaub et al, 2015 ; 2019 ; Figure 3B ) suggests that these AM nuclei are diploid at the onset of metamorphosis, something which remains to be ascertained. How to reconcile AM nuclear diploidy and AM growth could then be addressed.…”
Section: Trans-differentiation Of Ams At Metamorphosismentioning
confidence: 99%